Color Matching Strategies for Non‐Vital Discolored Teeth: Part 2. In‐Vivo Bleaching Options for Discolored Teeth Preparations. (20th April 2015) - Chu, Stephen J.; Mieleszko, Adam J.
Abstract: The following is a case report exemplifying the esthetic restorative and correction of a discolored substrate of a non‐vital maxillary right lateral and central incisor tooth. Frequently, clinicians are presented with discolored teeth preparations after removal of a restoration and face difficult decision‐making strategies in regards to materials selection, tooth preparation depth, and design. Part 2 will discuss the diagnosis and clinical bleaching treatment options when restoring non‐vital discolored substrate preparations. The key is to know when such techniques should and can be applied with the associated esthetic clinical results. Clinical Significance: Esthetic restorative correction of discolored teeth preparations can be clinically managed with an understanding of non‐vital bleaching concepts and techniques along with the associated risks and rewards.